CAR-iNKT cells: redefining the frontiers of cellular immunotherapy - Niedzielska, Magdalena; Chalmers, Amy; Popis, Martyna C.; Altman-Sharoni, Efrat; Addis, Stephen; Beulen, Rebekka; Rudqvist, Nils-Petter; Chantzoura, Eleni; Purbhoo, Marco A.; Chand, Dhan; Exley, Mark A. (Frontiers in Immunology, 2025)
Despite significant advances in cancer therapies, many malignancies remain resistant to current treatments due to complex immunosuppressive mechanisms, limited neoantigen expression, and dynamic tumor adaptations, underscoring the need for innovative therapeutic strategies. Adoptive cell therapy (ACT), particularly with chimeric antigen receptors (CARs and recombinant TCRs) targeting cancer-associated antigens, has emerged as a transformative strategy. However, conventional CAR-T cell therapies face substantial limitations such as manufacturing challenges, severe toxicities, and limited efficacy against solid tumors. Invariant natural killer T (iNKT) cells, a unique lymphocyte subset bridging innate and adaptive immunity, have emerged as a compelling alternative platform for CAR-based therapies, due to their distinctive ability to persist, penetrate in and remodel the tumor microenvironment (TME). Unlike conventional T cells, iNKT cells exhibit rapid activation without priming, potent cytotoxicity, and extensive immunomodulatory functions. Furthermore, the inherent immunomodulatory properties of iNKT cells through interactions with the monomorphic antigen-presenting molecule CD1d or stress ligands augment endogenous anti-tumor immunity by activating NK cells and cytotoxic T lymphocytes, promoting dendritic cell maturation, and reducing immunosuppressive myeloid cells, unlike other Innate T cells. CAR-engineered iNKT (CAR-iNKT) cells therefore leverage multiple targeting mechanisms through their native semi-invariant T-cell receptor (TCR), NK receptors (NKRs) and engineered CARs, enabling broader and more effective tumor recognition while actively reshaping immunosuppressive TME. Notably, iNKT cells lack alloreactivity, circumventing the risk of graft-versus-host disease (GvHD), positioning CAR-iNKT cells as ideal candidates for “off-the-shelf” allogeneic therapies that can overcome the limitations of existing immunotherapies.